Globalization and its challenges on educational policies in the Arab countries and suggested ways to confront them - Al Bashiti, Asmahan Sadeq (Journal of Educational and Psychological Sciences, 2022)
The study aimed to investigate the effects of globalization and its challenges on educational policies, and ways to confront them. The researcher used the documentary analytical descriptive research methodology. The tool was the analysis of a sample of primary and secondary documents issued during the period 2000-2020; The research may consist of three sections; The first topic: globalization and its effects on educational policies; The first requirement: conceptual definitions of globalization, the second requirement: the justifications for educational globalization, and the third requirement: globalization and its effects on educational and educational policies. The second topic: the most prominent challenges of globalization on educational policies and ways to confront them. The first requirement: the external and internal challenges of educational globalization, and the second requirement: ways to confront the educational challenges of globalization, the third requirement: the dimensions of educational policies in light of globalization, and the third topic: proposed structures for the educational educational process systems. One of the most prominent means of facing the challenges of globalization was; Finding a flexible educational system that allows diversification of paths, and real interest in the integrated holistic view in the formation of the citizen, instead of the limited partial view that focuses on educational aspects, and benefiting from modern technologies in education to open broad horizons for the individual to obtain knowledge, as well as active community participation among the educational media The researcher concluded with a conclusion that included the most important recommendations and proposals, foremost of which is crystallizing an integrated and clear educational philosophy, defining practical and realistic goals in line with developments, achieving the concept of sustainable education, and dedicating the concept of lifelong learning, as well as working on modernizing education in terms of its policies, goals, methods and purposes. and its subjects through the requirements of globalization.